Troxerutin as an anti-inflammatory and anti-oxidative drug could ameliorate Type 1 diabetes complications in C57BL/6 mice - Jafari-Khataylou, Y; Ahmadiafshar, S; Mirzakhani, N (Journal of the Hellenic Veterinary Medical Society, 2023)
Type 1 diabetes (T1D) is a chronic autoimmune disease that even with insulin therapy, inflammatory complications will develop in the long term. 40 inbred C57BL/6 mice were randomly divided into four groups (n=10): Control group consisted of healthy mice receiving citrate buffer, Diabetic group included a group of diabetic mice, Diabetic+TX group was a group of diabetic mice treated with troxerutin (TX), and TX group was a group of healthy mice treated with TX. Two weeks after the final dose of streptozotocin (STZ), The cytokine levels were measured using ELISA in the culture supernatants of spleen cells after 72 hours. Radioimmunoassay was used to measure insulin and c-peptide levels. The fasting blood sugar (FBS) was measured by an automatic glucometer device. lymphocyte proliferation index was evaluated using MTT assay, myeloperoxidase (MPO) level was measured in serum and pathologic studies of the kidney and liver were performed. The levels of IL-1, IL-17, TNF-α and IFN-γ as well as MPO, FBS levels and proliferation index was significantly decreased in the treated diabetic group compared to the diabetic mice (p<0.05). plasma C-peptide and insulin significantly increased in treated diabetic group than in the diabetic mice (p<0.05). Histologically, in diabetic animals treated with Tx, inflammatory and degenerative processes in both kidney and liver tissues were alleviated significantly (p<0.05). According to the results, it was supported the anti-diabetic and anti-inflammatory effects of TX, however, more studies are needed to investigate the effects of TX and the dose-response relationship in this disease.